2022
DOI: 10.1186/s12882-022-02909-1
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular myocardial mass index associated with cardiovascular and renal prognosis in IgA nephropathy

Abstract: Introduction In chronic kidney disease (CKD), like in IgA nephropathy (IgAN), cardiovascular (CV) mortality and morbidity are many times higher than in the general population, and left ventricular hypertrophy (LVH) is an independent risk factor for CV disease. This follow-up study investigated the association between left ventricular mass index (LVMI) and renal or cardiovascular outcomes. Methods We examined 118 IgAN patients prospectively. LVMI an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
1
3
1
Order By: Relevance
“…This phenomenon may be unique to all chronic glomerular diseases where patients have hypertension-induced LVH and deteriorating renal function, and they also have metabolic syndrome. Our previous data confirmed that these two cardiometabolic alterations cause higher cardiovascular morbidity and mortality [36,37]. So, it is indispensable to recognize the high CV risk of IgAN patients and treat them more aggressively to reduce their risk.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This phenomenon may be unique to all chronic glomerular diseases where patients have hypertension-induced LVH and deteriorating renal function, and they also have metabolic syndrome. Our previous data confirmed that these two cardiometabolic alterations cause higher cardiovascular morbidity and mortality [36,37]. So, it is indispensable to recognize the high CV risk of IgAN patients and treat them more aggressively to reduce their risk.…”
Section: Discussionsupporting
confidence: 68%
“…In our study, the K-M curve revealed that PLTs, the PLR, and the PAR were all significantly linked with the renal but not the cardiovascular outcomes of IgAN, indicating that each of them may be used as prospective predictors of renal endpoints, as Tan et al [12] reported in their cohort. In our previous studies, we found that the left ventricular mass index (LVMI) and the development of metabolic syndrome (MetS) in IgAN patients have an impact on cardiovascular outcomes [36,37]. Inflammatory parameters may indicate further factors that are responsible for the accelerated manifestation of the endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…An independent predictor of ESKD and CV events may be a higher LVMI. Increased LVMI should draw attention to CKD patients who require closer monitoring, referral for additional CV testing, and maximal renal and heart protection since they have a higher risk of cardiovascular and renal disease at an early stage of the disease (II-IV) [81]. In our current study, there was no significant difference in LVMI between the MetS and non-MetS groups.…”
Section: Discussioncontrasting
confidence: 44%
“…Similarly, LVMI assessed via echocardiography represented a potential prognostic factor in patients with IgA nephropathy, underling a correlation between high LVMI values, renal replacement therapy, and cardiovascular events [27].…”
Section: Discussionmentioning
confidence: 99%